Firing Weapons, § 5, Article 32-Profane Swearing and Disorderly Conduct, in The Code of the City of Annapolis (1897). - (:unkn) unknown (My University, 1897)
§ § "Sec. 5. Any person who shall discharge or fire off, any gun or other fire arms, or fire off or throw any fire crackers, chasers or other fireworks in said city, except when performing military duty, shall be fined not less than one nor more than twenty dollars, in the discretion of the Mayor, Counselor or Alderman, or Justice of the Peace before whom the same shall be tried."
Keywords: DISCHARGE